Hubungan Fungsi Kognitif dengan Tingkat Kemandirian Usia Lansia di Wilayah Puskesmas Mungka - Hurami, Nurul; Antara, Afrizal; Kanum, Sumairah (Media of Health Research, 2024)
The increasing number of elderly people reflects a rise in the average life expectancy, which can potentially lead to health issues. Among these is a decline in cognitive function, which may result in difficulties carrying out daily activities. If elderly individuals are unable to maintain independence, it can cause them to feel powerless, ill, and dependent on the assistance of others. The purpose of this study is to determine the relationship between cognitive function and the level of independence of the elderly in performing Activities of Daily Living (ADL) in the working area of the Mungka Public Health Center (Puskesmas). This study employs an observational analytical method with a cross-sectional design. The research sample was obtained through consecutive sampling, with a total of 51 elderly individuals residing in the working area of the Mungka Public Health Center. The research instruments used were the MoCA-Ina to measure cognitive function and the Katz Index to assess the level of independence in the elderly. The data analysis employed bivariate analysis using the chi-square statistical test. The study results showed that 20 elderly individuals (39.2%) experienced a decline in cognitive function, and 18 elderly individuals (35.3%) had moderate dependency. The statistical test results indicated a significant relationship between cognitive function and the level of independence in the elderly, with a p-value of 0.001 (<0.05). The conclusion of this study is that there is a significant relationship between cognitive function and the level of independence of the elderly in performing Activities of Daily Living (ADL) in the working area of the Mungka Public Health Center.